Seagrass Community At Kampung Ambong’s Water East Likupang Subdistrict, North Minahasa Regency - Surabi, Astevi; Kondoy, Khristin I. F.; Manu, Gaspar D. (Sam Ratulangi University, 2018)
This Research is done at Kampung Ambong’s Water East Likupang Subdistrict, North Minahasa Regency. The aim of this research is to know the type composition of seagrass and to analyzed soliding, dominatting index, various index, index of spreadness. The data taken with the line transect method. The transect placement divided become 3 transect line that located it uphold straight of beach line each of them 95 meter long. Meanwhile the space between one transect to another (second and third) each 100 m.Meanwhile the space between one transect to another (second and third) each 100 m. All of them identified as : Cymodocea rotundata, Syringodium isoetifolium, Halophila decipiens, Halodule pinifolia, Cymodocea serrulata, Enhalus acoroides, Halphila minor, Thalassia hempricii, Halodule uninervis, Halophila spinulosa. From the soliding each species show the highest score which is Cymodocea rotundata 2608 individu/m2, Syringodium isoetifolium 816 individu/m2, Halophila decipiens 420 individu/m2, Halodule pinifolia 292 individu/m2, Cymodocea serrulata 268 individu/m2, Enhalus acoroides 260 individu/m2, Halophila minor 224 individu/m2, Thalassia hempricii 160 individu/m2, Halodule uninervis 124 individu/m2, Halophila spinulosa 20 individu/m2.Whereas dominatting index be obtained 0.3 be in low category. its mean there is no species that to dominate in that water. Various index be obtained 1.65 be in mid category. it show that species community almost in spread condition, because it has the same opportunity.Index of spreadness be obtained 0.72 be in high category, because it has a mixing seagrass field.Keywords: community, composition, seagrass soliding. ABSTRAKPenelitian ini dilakukan di Perairan Kampung Ambong Kecamatan Likupang Timur Kabupaten Minahasa Utara.Tujuan dari penelitian ini mengetahui komposisi jenis lamun dan menganalisis kepadatan, indeks dominasi, indeks keanekaragaman, indeks kemerataan. Pengambilan data dilakukan dengan metode garis transek. Penempatan transek di bagi menjadi 3 garis transek yang di letakkan tegak lurus garis pantai dengan panjang masing-masing garis transek 95 meter. Sedangkan jarak antara transek 1 dengan transek yang lain (2 dan 3) masing-masing 100 m. Dari hasil penelitian komposisi jumlah spesies lamun (seagrass) adalah 10. Kesepuluh spesies yang teridentifikasi yaitu: Cymodocea rotundata, Syringodium isoetifolium, Halophila decipiens, Halodule pinifolia, Cymodocea serrulata, Enhalus acoroides, Halphila minor, Thalassia hempricii, Halodule uninervis, Halophila spinulosa.Kepadatan masing-masing spesies diperoleh menunjukkan nilai tertinggi yaitu Cymodocea rotundata 2608 individu/m2, Syringodium isoetifolium 816 individu/m2, Halophila decipiens 420 individu/m2, Halodule pinifolia 292 individu/m2, Cymodocea serrulata 268 individu/m2, Enhalus acoroides 260 individu/m2, Halophila minor 224 individu/m2, Thalassia hempricii 160individu/m2, Halodule uninervis 124individu/m2, Halophila spinulosa 20 individu/m2. Sedangkan indeks dominasi diperoleh 0.3 berada dalam kategori rendah, artinya tidak ada spesies yang mendominasi di perairan tersebut. Indeks keanekaragaman diperoleh 1.65 berada dalam kategori sedang. Hal ini menunjukkan bahwa komunitas spesies dalam kondisihampir merata, karena memiliki peluang yang sama. Indeks kemerataan diperoleh 0.72 berada dalam kategori tinggi, karena memiliki padang lamun campuran.Kata kunci : komunitas, komposisi, kepadatan lamun.